BUDAYA ORGANISASI DAN KINERJA KARYAWAN DIMEDIASI KOMITMEN ORGANISASIONAL - Utami, Esti Margiyanti; Bandiastuti, Febrianti Nur (STAI Darul Qalam Tangerang, 2023)
Employees are a key factor in achieving company goals. Good employee management will optimize employee work results. Employee performance improvement can be done by taking into account various factors that affect employee performance, including organizational culture and organizational commitment. This study examines the role of organizational commitment in mediating organizational culture and employee performance. The population in this study were employees of PT.URW Purworejo. Sampling using purposive sampling technique. The sample taken amounted to 126 employees. The research data was collected using a questionnaire, which was then tested for mediation with a causal step approach.The results of data analysis show that organizational culture has a positive effect on employee performance, organizational commitment has a positive effect on employee performance, and organizational commitment mediates the influence of organizational culture on employee performance